Tratamiento de la noticia deportiva sobre el campeón del giro de Italia 2019, Richard Carapaz en el medio Televisivo Ecuavisa y sus redes sociales - Chantera Riascos, Williams Antonio (2019)
The present case study called "TREATMENT OF THE SPORTS NEWS ON THE CHAMPION OF THE TOUR OF ITALY 2019, RICHARD CARAPAZ IN THE TELEVISIVE MEDIA ECUAVISA AND ITS SOCIAL NETWORKS". the local press and social networks about this beginning; in order to know the theoretical elements that sustain the life of the athlete from the beginning of competition, as well as the dissemination of this great conquest. On the other hand, a description is made of the key concepts that underpin the study; For this, a qualitative methodology has been used through the use of historical criticism, open signal channels, news from social networks, which will obtain all the appropriate conclusions to the researcher without the need to resort to statistics and numerical figures; techniques such as observation and analysis of social media stories about the news were used; What identified to identify the level of impact that this news had in the country and the international level. It is evident that 80% of the population that follows the social networks that have the repetitions of the sporting feat, compared to the disadvantage that exists in conventional television where the news only appears and then is not repressed. As a result, it was possible to determine as a conclusion that when athletes conquer the local press, written, television or through the use of social networks internationally, favor the prompt dissemination of the same, document and remember when it is considered pertinent, being a trend in The new journalistic style.